Substitution effects in parental investments - Loren Brandt; Aloysius Siow; Hui Wang (Institute for the Study of Labor (IZA), 2009)
The paper estimates how parents adjust bride-prices and land divisions to compensate their sons for differences in their schooling investments in rural China. The main estimate implies that when a son receives one yuan less in schooling investment than his brother, he will obtain 0.7 yuan more in observable marital and post-marital transfers as partial compensation. Controlling for unobserved household heterogeneity, planned consumption differences across sons, and a fuller accounting of lifetime transfers are quantitatively important. The empirical findings strongly support the unitary model as a model of resource allocation for sons in traditional agricultural families.
Keywords: D13; J12; J13; 330; Household model; parental investment; marriage market; transfers; Familienökonomik; Haushaltsökonomik; Eltern; Kinder; Bildungsinvestition; Ehe; Privater Transfer; Ländlicher Raum; China